Effects of water-washing Saccharina japonica on fast pyrolysis in a bubbling fluidized-bed reactor. (March 2017) - Choi, Jae Hyung; Kim, Seung-Soo; Ly, Hoang Vu; Kim, Jinsoo; Woo, Hee Chul
Abstract: The pyrolysis characteristics of non-edible Saccharina japonica ( S. japonica ) obtained from an offshore high-density aquaculture facility were systematically investigated using a thermogravimetric analyzer and a bubbling fluidized-bed reactor. As high mineral contents in S. japonica cause ash fouling or agglomeration of char and bed material in fluidized-bed reactor, S. japonica was water-washed as pre-treatment to remove minerals and sticky materials. The pretreated S. japonica samples were mostly decomposed between 200 and 350 °C at heating rates of 5–20 °C/min. The calculated activation energy increased from 36.31 to 393.01 kJ/mol when pyrolysis conversion increased from 5 to 60%. The yields of bio-oil were 25.57–31.27 wt% under the investigated pyrolysis conditions (temperature: 350–450 °C; fluidization velocity: 2.0 × Umf − 4.5 × Umf ). The highest bio-oil yield (31.27 wt%) from water-washed S. japonica was obtained at 375 °C and 4.0 × Umf, and the HHVs of the organic and aqueous phases in the bio-oil were 31.47 and 5.41 MJ/kg, respectively. The major compounds in the bio-oil were analyzed by GC-MS and the carbon number distribution of the bio-oils was determined through simulated distillation by TGA. Highlights: Pyrolysis characteristics and activation energy of water-washed S. japonica were investigated. Fast pyrolysis of water-washed S. japonica was carried out in a bubbling fluidized-bed reactor. The highest bio-oil yield of 31.27 wt% was obtained at 350 °C and 4.0 Umf . The HHVs of the organic and aqueous bio-oils were 31.47 and 5.41 MJ/kg, respectively.